2020
DOI: 10.1111/jcmm.15476
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic adenosine monophosphate elevating medicine, forskolin, reduces neointimal formation and atherogenesis in mice

Abstract: Neointimal formation and atherogenesis are major vascular complications following percutaneous coronary intervention, and there is lack of pharmacological therapy. This study was aimed to examine the effect of forskolin (FSK), a cyclic adenosine monophosphate (cAMP)‐elevating agent, on vascular response to angioplasty wire injury and on atherogenesis in mice. Forskolin treatment reduced neointima formation at 7 and 28 days after wire injury. Early morphometrics of the injured vessels revealed that FSK treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Notably, in 12 patients with stage III (NYHA) congestive cardiomyopathy, forskolin dose-dependently reduced cardiac pre-and afterload values, and led to a reduction in systolic, diastolic, and mean pulmonary artery pressures as well as pulmonary wedge pressure by >50% concomitant with an increase in cardiac output (Baumann et al, 1990). Consistent with a recent report (Hao et al, 2020) from Hao et al, this study demonstrates the ability of forskolin to promote endothelial recovery from vascular injury and indicates its therapeutic applications in disorders associated with vascular injuries, such as in-stent restenosis after treatment for coronary stenosis.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, in 12 patients with stage III (NYHA) congestive cardiomyopathy, forskolin dose-dependently reduced cardiac pre-and afterload values, and led to a reduction in systolic, diastolic, and mean pulmonary artery pressures as well as pulmonary wedge pressure by >50% concomitant with an increase in cardiac output (Baumann et al, 1990). Consistent with a recent report (Hao et al, 2020) from Hao et al, this study demonstrates the ability of forskolin to promote endothelial recovery from vascular injury and indicates its therapeutic applications in disorders associated with vascular injuries, such as in-stent restenosis after treatment for coronary stenosis.…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that only free cholesterol can be transported by cholesterol transporters in the lysosome such as Niemann–Pick type C related protein 1 or 2 (NPC-1 or NPC-2) for further metabolism and efflux intracellularly; once the free cholesterol is converted into CCs, they cannot be transported by NPC-1 or NPC-2, leading to the accumulation of massive CCs in the lysosome and cell apoptosis. , Therefore, the prevention of CC formation or the dissolution of CCs to free cholesterol in the lysosome to enhance the disposal of cholesterol will be of great clinical significance for atherosclerotic therapy. As confirmed by a recent study, the development of atherosclerosis can be halted by the treatment of cAMP-enhancing agents (such as forskolin, which catalyzes the production of cAMP, , and rolipram, which prevents the degradation of cAMP) to inhibit the formation of CCs and promote cholesterol efflux in endothelial cells . However, for macrophages or foam cells, which are the major cholesterol-laden cells in atherosclerotic plaque, none of the clinical drugs have been used to remove lysosomal CCs in macrophages or foam cells for the treatment of atherosclerosis.…”
mentioning
confidence: 99%
“…To examine the effect of RIPK1 inhibition on the development of advanced atherogenesis, we used a mouse model ( ApoE SA / SA ) that exhibits both hypercholesterolemia and hypertension upon induction and develop advanced atherosclerotic lesions including those in coronary arteries ( 20 ). Eight-week-old male ApoE SA / SA mice were administered with a western diet (21% fat and 0.2% cholesterol) mixed with or without GSK547 at a dose of 10 mg/kg/day, and with doxycycline (Dox)-containing water to induce hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Eight-weeks-old male and female ApoE SA / SA mice on C57BL/6J background, which are deficient in Apoe gene and with SR-BI knockdown and inducible angiotensin II expression (by doxycycline administration) were used in the present study ( 20 ). For atherosclerosis study, ApoE SA / SA mice were fed a Western diet (TD 88137; Harlan Teklad) which contains GSK547 powder [GlaxoSmithKline; 10 mg/kg/day (0.083 g/kg food)].…”
Section: Methodsmentioning
confidence: 99%